sIL-6R is related to weekly training mileage and psychological well-being in athletes - Cullen, T.; Thomas, A. W.; Webb, R.; Phillips, T.; Hughes, M. G. (Medicine & Science in Sports & Exercise, 2017)
INTRODUCTION: Interleukin 6 (IL-6) has been ascribed both positive and negative roles in the context of exercise and training. The dichotomous nature of IL-6 signaling seems to be determined by the respective concentration of its receptors (both membrane-bound [IL-6R] and soluble [sIL-6R] forms). The purpose of the present study was to investigate the response of sIL-6R to long-term training and to investigate the relationship between sIL-6R, self-reported measures of well-being, and upper respiratory symptoms in highly trained endurance athletes.